2021
DOI: 10.3389/fsufs.2021.657744
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Smallholder Farmer's Participation in the Wheat Value Chain in North-West Mt. Kenya

Abstract: Wheat is the second most important carbohydrate staple in Kenya and is produced by both smallholder and large-scale farmers. Smallholders are the majority, but produce <20% of the total national production. Compared to large-scale farmers, they have been considered to be less efficient producers and thus fail to benefit fully from their participation in the wheat value chain. This study aims at establishing the value accruing to smallholder and large-scale farmers participating in wheat production in no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The fi ndings of the research indicated that 57.50% of the participants identifi ed as male, with an estimated mean age of 45 years. Consistent with the fi ndings of [4,10] the average age of the participants was also reported to be 45 years. Concerning the respondents' marital status, 11.67%were divorced, 24.17%…”
Section: Socioeconomic Characteristics Of the Respondents In The Stud...supporting
confidence: 81%
See 2 more Smart Citations
“…The fi ndings of the research indicated that 57.50% of the participants identifi ed as male, with an estimated mean age of 45 years. Consistent with the fi ndings of [4,10] the average age of the participants was also reported to be 45 years. Concerning the respondents' marital status, 11.67%were divorced, 24.17%…”
Section: Socioeconomic Characteristics Of the Respondents In The Stud...supporting
confidence: 81%
“…It depicts a household's ability to withstand price rises while yet being productive by investing in health care, education, tools, and other productive assets for its members. Households that spend more than 65% of their total expenditure on food are vulnerable in this regard because such a high percentage implies that the household is forced to choose between meeting their food and non-food needs or reducing consumption of one or both to below their needs [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second popular method used by authors was a statistical analysis to evaluate strategies for improving FVCs, RFHs, and alternative food distribution networks. Statistical analysis was used to understand gender perspectives on FVCs, economic and social sustainability, farmer regeneration, and consumer perspectives on local food [63][64][65][66][67][68][69][70][71][72]. The tools commonly used for statistical analysis were SPSS and the software ANOVA.…”
Section: Analysis Of Research Methodology Used In Food Value Chain An...mentioning
confidence: 99%
“…Hence, a few scholars discussed FVCs in the context of global issues, such as business strategy, knowledge, and capacity building [51,90]. The review showed that FVCs were seen more as a strategy that can be adopted to develop region's potential rather than to develop a food network at the global level [64,75,91]. Research topics often discussed by researchers related to FVC were mostly related to the development of upstream food actors.…”
Section: Food Value Chains and Their Relationship With Sustainable Lo...mentioning
confidence: 99%